Iran's Qods force : proxy wars, terrorism, and the war on America - Sirrs, Owen L. (Naval Institute Press, 2022)
"Owen Sirrs analyzes how Iran uses unconventional warfare to try to achieve one of its most cherished objectives, hegemony over the Middle East, and demonstrates how U.S. policymakers and warfighters were repeatedly stymied by Iran's unconventional warfare strategy, which straddled the threshold between conventional and covert warfare"--